FAMILY SUCCESSION IN THE MANAGEMENT OF BRAZILIAN DAIRY FARMING: TECHNOLOGICAL AND MANAGERIAL CHALLENGES ON SMALL PROPERTIES (REMUNOM, 2026)
This article analyzes the challenges faced by small family farms in Brazilian dairy farming, focusing on the technological and managerial transformations necessary to ensure family succession. Economic and financial viability can be achieved through the gradual adoption of technologies—such as robotic milking and management software — combined with more professional administrative practices. This modernization increases profitability and provides a better quality of life, making the activity attractive to new generations. Based on recent literature review, limitations of a structural, economic, and cultural nature are identified, which hinder the implementation of mod-ern technologies and efficient management. It is concluded that it is essential to adapt management models to local realities, strengthen institutional support, and incorporate innovations such as robotic milking and specialized systems to ensure the sustainability and appeal of dairy activity to successors.